2017
DOI: 10.30699/ijp.2017.27993
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of Common Antibiotics Used to Treat Staphylococcus aureus on Biofilm Formation

Abstract: Background & Objective: Staphylococcus aureus, especially methicillin-resistant S. aureus (MRSA), represent serious nosocomial and community infections. Biofilm formation as an important virulence factor may be affected by sub-inhibitory levels of antibiotics. Few studies examined the effects of all therapeutic antimicrobial agents on clinical S.aureus. The current study aimed at observing the inducing and reducing effects of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Owing to the emergence of multidrug-resistant S. aureus and an increasing trend, many research efforts have begun to shift the focus on how to reduce the virulence of S. aureus instead of the traditional through removing pathogens. In recent years, many studies have demonstrated that subinhibitory concentrations of antibiotics have an effect on S. aureus virulence factors (Otto et al, 2013) and biofilm formation (Majidpour et al, 2017). But it is more than subinhibitory antibiotics enhancing the virulence of S. aureus (Hodille et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the emergence of multidrug-resistant S. aureus and an increasing trend, many research efforts have begun to shift the focus on how to reduce the virulence of S. aureus instead of the traditional through removing pathogens. In recent years, many studies have demonstrated that subinhibitory concentrations of antibiotics have an effect on S. aureus virulence factors (Otto et al, 2013) and biofilm formation (Majidpour et al, 2017). But it is more than subinhibitory antibiotics enhancing the virulence of S. aureus (Hodille et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…25 Biofilm presence should also influence antibiotic choice; in one recent study, the effects of ten antibiotics commonly used against S. aureus were evaluated at various doses (0.06-128 µg/mL). 26 At subminimum inhibitory concentrations (MICs), linezolid appeared most effective in clearing biofilm. Conversely, azithromycin, vancomycin, oxacillin, cotrimoxazole, minocycline, and clindamycin induced biofilm in some of the bacterial strains tested.…”
Section: Surgical Debridement and Antibioticsmentioning
confidence: 99%
“…Conversely, azithromycin, vancomycin, oxacillin, cotrimoxazole, minocycline, and clindamycin induced biofilm in some of the bacterial strains tested. 26 An alternative, more effective approach to antibiotic monotherapy is combination antibiotics. [27][28][29] Rifampin has been studied in combinations with linezolid, vancomycin, cloxacillin, and ciproflaxin.…”
Section: Surgical Debridement and Antibioticsmentioning
confidence: 99%
“…Generally, antibiotics reduced biofilm formation; however, several studies showed that the antibiotics could significantly induce biofilm formation depending on antibiotics class and the bacterial strain [31]. A study accomplished by Majidpour et al [8] demonstrated when MRSA isolates exposed to sub MIC of azithromycin and vancomycin could significantly induce the biofilm formation at least of two isolates, and such as these results may cause an adverse effect on the course of treatment. Similarly, Ozturk et al [32] indicated that some antibiotics may induce the biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…The growing knowledge of bacterial virulence and pathogenesis highlights new horizons for the development of novel and alternative treatment choices by attenuating bacterial virulence involving biofilm [4]. Furthermore, the exposure of bacteria to antibiotics at sub MIC may usually take place during antibiotic therapy [8]. Hence, the present work aimed to understand the interconnection among hemolysins, biofilm, and gentamicin resistance in local MRSA isolates.…”
Section: Introductionmentioning
confidence: 99%